Research on Molecular Mechanism of Fructus Ligustri Lucidi against Osteoporosis based on Network Pharmacology (Brazilian Journal of Pharmaceutical Sciences, 2022)
This study aimed to investigate the molecular mechanism of Fructus Ligustri Lucidi (NZZ, Chinese abbreviation) against osteoporosis (OP) by means of network pharmacology.ChemDraw Professional 15.1 software and Molinspiration Smiles database were used to draw the chemical formulas of the components. The active ingredients and related target proteins of NZZ were searched in platform of systematic pharmacology of traditional Chinese medicine database, Drugbank, Therapeutic Target Database, SymMap and other databases. Gene Ontology(GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were carried out on the selected target through Enrichr and KEGG Automatic Annotation databases, and their mechanism was studied. A total of 29 compounds and 140 corresponding targets, including 14 key targets and 14 protein factors in protein-protein interaction core network were obtained. The key targets were tumor necrosis factor(TNF), interleukin(IL)-6R and sestrogen receptor alpha. The number of GO items was 466 (P<0.05), including 399 items of biological process (BP), 54 items of cell composition (MF) and 13 items of molecular function (CC). KEGG pathway enrichment screened 85 signaling pathways (P<0.05), including the IL-17 signaling pathway, TNF signaling pathway, advanced glycation end products and their receptors signaling pathway and cAMP signaling pathway. The active ingredients of NZZ. exert their anti-OP effects through multi-components, multi-targets and multi-pathways, which can provide new evidence for further study of their anti-OP mechanism.